Identification of an Autophagy-Related Gene Signature for the Prediction of Prognosis in Early-Stage Colorectal Cancer - Lin, Xu-tao; Wu, Qiu-ning; Qin, Si; Fan, De-jun; Lv, Min-yi; Chen, Xi; Cai, Jia-wei; Weng, Jing-rong; Zou, Yi-feng; Rong, Yu-ming; Gao, Feng (Frontiers in Genetics, 2021)
Purpose. A certain number of early-stage colorectal cancer (CRC) patients suffer tumor recurrence after initial curative resection. In this context, an effective prognostic biomarker model is constantly in need. Autophagy exhibits a dual role in tumorigenesis. Our study aims to develop an autophagy-related gene (ATG) signature based on high-throughput data analysis for disease-free survival (DFS) prognosis of patients with stage I/II CRC. Methods. Gene expression profiles and clinical information of CRC patients extracted from four public datasets were distributed to discovery and training cohort (GSE39582), validation cohort (TCGA CRC, n=624), and meta-validation cohort (GSE37892 and GSE14333, n=420). Autophagy genes significantly associated with prognosis were identified. Results. Among 655 autophagy-related genes, a 10 gene ATG signature, which was significantly associated with DFS in the training cohort (HR, 2.76[1.56–4.82]; P=2.06×10-4), was constructed. The ATG signature, stratifying patients into high and low autophagy risk groups, was validated in the validation (HR, 2.29[1.15–4.55]; P=1.5×10-2) and the meta-validation cohorts (HR, 2.5[1.03–6.06]; P=3.63×10-2), and proved to be prognostic in a multivariate analysis. Functional analysis revealed enrichment of several immune/ inflammatory pathways in the high autophagy risk group, where increased infiltration of T regulatory cells (Tregs) and decreased infiltration of M1 macrophages were observed. Conclusions. Our study established a prognostic ATG signature that effectively predicted DFS for early-stage CRC patients. Meanwhile, the study also revealed the possible relationship among autophagy process, immune/ inflammatory response and tumorigenesis.